Economic Abuse: A Subtle but Common Form of Power and Control - Christy, Kameri (Journal of interpersonal violence, 2022)
Awareness of and responses to intimate partner violence against women (IPV-W) have been increasing steadily since the early 1970s. However, one of the most frequently used and effective strategies by abusive partners, economic abuse (EA), has received much less attention than physical or sexual abuse. In-depth qualitative interviews were conducted with IPV-W service users (n = 15) and providers (n = 24) in England to expand the knowledge-base and provide support regarding the reality and impact of EA, the economic barriers and supports experienced when trying to obtain help, and recommendations for remediating EA. Grounded theory procedures of open, axial, and selective coding techniques were utilized for data analysis. Five themes, (a) definitions and prevalence of EA, (b) service users experiences of EA, (c) continued impact of EA, (d) barriers to obtaining help, and (e) goals regarding finances, emerged with both groups. The theme professional responses to EA also surfaced for service providers, and service users discussed the additional theme of service users? support when experiencing EA. The study participants? recommendations include (a) identifying EA as a distinct type of IPV-W, (b) updating legal guideline to allow offenders of EA to be prosecuted, (c) encouraging banks to do more to assist victims of EA, and (d) updating police training and frontline workers to include EA. The narratives of the study participants underscore the import of collaboration with and involvement of IPV-W service user and provider stakeholders when developing and implementing policies, programs, and practices to prevent further EA and meet the distinctive needs of women who experience EA as a part of IPV-W.